Webar Application For An Air Quality System In IOT-Based Smart Environement - Badouch, Abdessamad; Krit, Salahddine (International Journal of Membrane Science and Technology, 2023)
Augmented Reality (AR) and the Internet of Things (IOT) are trending technologies that have gained popularity in smart cities. In this paper, we propose a non-expansive and uncomplicated prototype that combines the two technologies, namely, the Internet of Things and Augmented Reality, to build an air quality monitoring system for a smart environment. The webAR application developed can be used on any device, and it control measurements of temperature, humidity, and air quality data collected from multiple IOT devices. In addition to the ease of use and speed of loading compared to other applications, our prototype offers an application that does not require installation, a major factor that limits user use. Finally, the paper indicates the prospects of these technologies and the challenges their development is facing.